1995
DOI: 10.1007/bf01271545
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of [3H]clozapine binding sites in rat brain

Abstract: We examined the characteristics of [3H]clozapine binding sites in four rat brain regions (frontal cortex, limbic area, hippocampus and striatum) in order to elucidate the pharmacological profile of this unique atypical antipsychotic drug. The specific [3H]clozapine binding was found to be saturable and reversible in all these brain regions. Scatchard analysis of the saturation data indicated that the specific binding consisted of high- and low-affinity components. Displacement experiments showed that the musca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…It binds to dopaminergic, serotonergic, H1 histaminergic, muscarinic acethylcholine, and α1-and α2-adrenergic receptors (King and Waddington, 2004;Leysen, 2000). Clozapine has relatively low affinity for the D2 receptors in the striatum (Xiberas et al, 2001), while its in vitro affinity for the D4 receptors is much higher than that for D1, D2, D3, and D5 receptors (Coward, 1992;Kusumi et al, 1995). This accounts for the efficacy of clozapine in alleviating the symptoms of schizophrenia without causing extra pyramidal side effects (Farde et al, 1992), because D4 receptor density is high in the frontal cortex and amygdala but relatively low in the basal ganglia (De La Garza and Madras, 2000;Tarazi et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…It binds to dopaminergic, serotonergic, H1 histaminergic, muscarinic acethylcholine, and α1-and α2-adrenergic receptors (King and Waddington, 2004;Leysen, 2000). Clozapine has relatively low affinity for the D2 receptors in the striatum (Xiberas et al, 2001), while its in vitro affinity for the D4 receptors is much higher than that for D1, D2, D3, and D5 receptors (Coward, 1992;Kusumi et al, 1995). This accounts for the efficacy of clozapine in alleviating the symptoms of schizophrenia without causing extra pyramidal side effects (Farde et al, 1992), because D4 receptor density is high in the frontal cortex and amygdala but relatively low in the basal ganglia (De La Garza and Madras, 2000;Tarazi et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…P450 26B1 and the recently described P450 46B1 are involved in the metabolism of the endogenous substances all-trans retinoic acid and cholesterol, respectively (Bogdanovic et al, 2001;Trofimova-Griffin and Juchau, 2002;Mast et al, 2003). Drugs used in treatment of common neurological and mental diseases (e.g., clozapine, phenytoin, and antidepressants) exhibit specific function in certain brain regions (Kusumi et al, 1995;Riedl et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The method for membrane processing and for each receptor binding assay was reported previously (Meltzer et al, 1989;Kusumi et al, 1995). Briefly, the tissue was homogenized in 50mM Tris-HC1 buffer (pH 7.7 at 25~ containing 5mM EDTA using a Polytron (setting 6, 20 sec).…”
Section: Receptor Binding Assaymentioning
confidence: 99%
“…We have previously reported that the D 4 receptor binding sites can be detected in rat frontal cortex by means of a [3H]clozapine binding method (Kusumi et al, 1995). Since no D 4 specific radioligand is presently available, the D 4 receptor component is measured indirectly from displacement experiments using nemonapride.…”
Section: Introductionmentioning
confidence: 99%